Usability Analysis of an Electronic Immunization Monitoring and Logistics System using PIECES and SUS - Citra Yustitya Gobel; Misrawati Aprilyana Puspa; Syarifah Fitrah Ramadhani; Siti Andini Utiarahman; Sinta Suleman (SISTEMASI, 2026)
The Electronic Immunization Monitoring and Logistics System (SMILE) is an information system designed to support the integrated management of immunization records and healthcare logistics. The successful implementation of such a system depends not only on its functionality but also on its usability, which significantly influences user satisfaction and acceptance. This study aims to evaluate the usability of the SMILE application using the PIECES framework—covering Performance, Information, Economy, Control, Efficiency, and Service—and the System Usability Scale (SUS). A descriptive quantitative approach was employed, with data collected through observations, a literature review, and questionnaire surveys administered to 56 users of the SMILE application at the Gorontalo Provincial Health Office. The results of the PIECES analysis indicate that all evaluation dimensions achieved the "Satisfied" category, with mean scores of 3.68 for Performance, 4.28 for Information, 4.36 for Economy, 4.26 for Control, 4.25 for Efficiency, and 4.25 for Service. The usability assessment using the SUS yielded an average score of 53, which falls within the "OK" adjective rating (score range: 51–67) and the "Marginal" acceptability category. According to the SUS grading scale, this score corresponds to Grade D, indicating that the application's overall usability requires improvement. Although users expressed satisfaction with the system's performance and service quality, the findings suggest that enhancements are still needed, particularly in terms of ease of use, navigation, and overall user experience. The findings of this study provide valuable insights and practical recommendations for developers to improve the quality and usability of the SMILE application, thereby supporting more effective adoption and use in healthcare services.